IMPLEMENTASI KEBIJAKAN PEMBANGUNAN DESA WISATA BERKELANJUTAN: (Studi Kasus Destinasi Wisata Penyangga Zona Kawah Ijen Desa Adat Osing Kemiren, Kecamatan Glagah, Kabupaten Banyuwangi) - Muhamad Nanda Al Hakim Akbar; Endah Setyowati; Sujarwoto (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2022)
Tourism is one sector that plays an important role in the process of development and development of an area, especially for improving the community's economy, conservation cultural customs, and environmental conservation. Tourism development also has negative impacts such as depletion of natural resources, causing pollution, and environmental problems. The need for sustainable development in the economic, customary and cultural aspects, as well as the environment in the tourism sector. The development of tourist villages is a form of sustainable development. Banyuwangi Regency Regulation Number 1 of 2017 concerning Tourism Villages as a regulation for tourism village development in Banyuwangi Regency. However, there are still environmental problems in the development of the Osing Kemiren Traditional Village. This research uses a qualitative approach with a case study method. Data collection techniques by means of observation, interviews, and documentation. The results of this study indicate that environmental problems occur due to differences in interests between actors implementing policies, the existence of institutions and authorities who are less supportive in supervising the development of tourist villages, as well as responsiveness and compliance of people who do not understand the development of tourist villages.